2017
DOI: 10.1021/jacs.6b11950
|View full text |Cite
|
Sign up to set email alerts
|

Strong Localization of Anionic Electrons at Interlayer for Electrical and Magnetic Anisotropy in Two-Dimensional Y2C Electride

Abstract: We have synthesized a single crystalline YC electride of centimeter-scale by floating-zone method and successfully characterized its anisotropic electrical and magnetic properties. In-plane resistivity upturn at low temperature together with anisotropic behavior of negative magnetoresistance is ascribed to the stronger suppression of spin fluctuation along in-plane than that along the c-axis, verifying the existence of magnetic moments preferred for the c-axis. A superior magnetic moment along the c-axis to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
92
1

Year Published

2017
2017
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 86 publications
(99 citation statements)
references
References 25 publications
6
92
1
Order By: Relevance
“…It was recently reported that the layer structured [Ca 2 N] + •e − electride showed an extremely high mobility as well as distinct anisotropic properties in electrical transport and work function, which were ascribed to the fully delocalized high-density IAEs (1.39 × 10 22 cm −3 ) confined in two-dimensional (2D) interlayer space. The layer structured [Ca 2 N] + •e − electride was referred to as "2D electride" 8 , triggering the development of various 2D electrides [11][12][13][14] .…”
mentioning
confidence: 99%
“…It was recently reported that the layer structured [Ca 2 N] + •e − electride showed an extremely high mobility as well as distinct anisotropic properties in electrical transport and work function, which were ascribed to the fully delocalized high-density IAEs (1.39 × 10 22 cm −3 ) confined in two-dimensional (2D) interlayer space. The layer structured [Ca 2 N] + •e − electride was referred to as "2D electride" 8 , triggering the development of various 2D electrides [11][12][13][14] .…”
mentioning
confidence: 99%
“…19 The Y 2 C electride was also realized experimentally and furthered our understanding of the interplay between magnetism and localized electrons. [20][21][22][23] These findings of inorganic electrides provide new possibilities for both fundamental science and applications.…”
Section: Introductionmentioning
confidence: 96%
“…Despite many endeavors since the first crystalline electride grown three decades ago, 3 only a few electrides have been synthesized. [4][5][6][7][8][9][10][11][12][13] The first room-temperature stable inorganic electride was reported in 2003 by removing oxygen ions from the crystallographic cages of 12CaO.7Al 2 O 3 , yielding [Ca 24 Al 28 O 64 ] 4+ (4e -). 5 The high density of anionic electrons with loosely bounded nature makes [Ca 24 Al 28 O 64 ] 4+ (4e -) promising for a plethora of applications, such as efficient thermionic emitters, 14 electroninjection electrode for organic light-emitting diodes, 15,16 and high performance catalysts.…”
Section: Introductionmentioning
confidence: 99%